Longer Poly(U) Stretches in the 3′UTR Are Essential for Replication of the Hepatitis C Virus Genotype 4a Clone in in vitro and in vivo - Takagi, Asako; Amako, Yutaka; Yamane, Daisuke; Kitab, Bouchra; Tokunaga, Yuko; El-Gohary, Ahmed; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Microbiology, 2021)
We established an infectious hepatitis C virus (HCV) clone in vitro and in vivo, from an Egyptian patient with chronic HCV infection and hepatocellular carcinoma (HCC). First, we inoculated patient plasma into a humanized chimeric mouse. We observed HCV genotype 4a propagation in the chimeric mouse sera at 1.7× 107 copies/mL after 6 weeks (#182). Next, we cloned the entire HCV sequence from these HCV-infected chimeric mouse sera using RT-PCR, and 5′ and 3′ RACE methodologies. We obtained a shorter clone (HCV-G4 KM short, GenBank: AB795432.1), which contained 9,545 nucleotides with 341 nucleotides of the 5′-UTR and 177 nucleotides of the 3′-UTR. We also obtained a longer clone by dividing the HCV genome into three fragments and the poly (U) sequences. As a result, we obtained a longer 3′-UTR sequence than that of the HCV-G4 KM short clone, which contained 9,617 nucleotides. This longer clone possessed a 3′-UTR of 249 nucleotides (HCV-G4 KM long, GenBank: AB795432.2), because of a 72-nucleotide longer poly (U) stretches. The HCV-G4-KM long clone, but not the HCV-G4-KM short clone, could establish infection in human hepatoma HuH-7 cells. HCV RNAs carrying a nanoluciferase (NL) reporter were also constructed and higher replication activity was observed with G4-KM long-NL in vitro. Next, both short and long RNAs were intra-hepatically injected into humanized chimeric mouse. Viral propagation was only observed for the chimeric mouse injected with HCV-G4 KM long RNA in the sera after 21 days (1.64 × 106 copies/mL) and continued until 10 weeks post inoculation (wpi; 1.45–4.74 × 107 copies/mL). Moreover, sequencing of the HCV genome in mouse sera at 6 wpi revealed the sequence of the HCV-G4-KM long clone. Thus, the in vitro and in vivo results of this study indicate that the sequence of HCV-G4-KM long RNA is that of an infectious clone.